2010
DOI: 10.1080/02786826.2010.497513
|View full text |Cite
|
Sign up to set email alerts
|

Sampling and Retention Efficiencies of Batch-Type Liquid-Based Bioaerosol Samplers

Abstract: Four commercially available batch-type bioaerosol samplers, which collect time-integrated samples in liquids, were evaluated. Sampling efficiency was characterized as a function of particle size using near-monodisperse polystyrene spheres (sizes of 1-5 µm) and oleic acid droplets (3-10 µm). Results show the sampling efficiency of AGI-30 impingers range from 4-67% for particle sizes of 1 to 5.1 µm with significant variations between units; those of SKC BioSampler impingers range from 34-105% for particle sizes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 21 publications
(17 reference statements)
1
48
0
Order By: Relevance
“…The lower dose ratio values for the 1 µm PSL particles were likely a result of the greater adherence of those particles to the inner walls of the PDC. Kesavan et al (2010) observed a similar phenomenon with 1 µm PSLs in bioaerosol samplers that collected time-integrated hydrosol samples.…”
Section: Effect Of Number Of Actuations On Psl Dose Outputmentioning
confidence: 65%
“…The lower dose ratio values for the 1 µm PSL particles were likely a result of the greater adherence of those particles to the inner walls of the PDC. Kesavan et al (2010) observed a similar phenomenon with 1 µm PSLs in bioaerosol samplers that collected time-integrated hydrosol samples.…”
Section: Effect Of Number Of Actuations On Psl Dose Outputmentioning
confidence: 65%
“…If the composition of microorganisms in the sample stays the same as in the ambient air, the sampling efficiency is not all that important for determining microbial diversity as long as enough material can be collected for further analysis. However, different samplers also perform differently as a function of particle size (Kesavan et al 2010;King et al 2009). This is considerably more serious, since if the size of collected particles changes with sampling approach, the results will inevitably be affected since the diameter of airborne microorganisms can vary from tens of nanometers to one hundred micrometer (Wittmaack et al 2005).…”
Section: Discussionmentioning
confidence: 98%
“…However, the extant studies use various sampling approaches, which complicates the comparison of microbial communities, diversity, and ecology. While many studies have compared the sampling efficiency of different aerosol collectors (Fields et al 1974;Jensen et al 1992;Kesavan et al 2010;King et al 2009;Whyte et al 2007), no study, to the best of our knowledge, has addressed how the sampling strategy can affect apparent microbial diversity of air samples. Since different devices have different particle cut-off diameter, the choice of sampling technique may certainly affect the composition of the sampled community; let alone the most common bacteria may range in diameter from 0.1 to 5 lm, while airborne fungal spores and algae are typically 5-15 lm and may be as large 100 lm (Tormo et al 2001;Wittmaack et al 2005).…”
Section: Introductionmentioning
confidence: 94%
“…Possible reasons for the lower concentration value measured with the impinger vis·a·vis the Andersen are greater wall losses in the impinger for some of the larger particles and a loss of both cells and culturability in the hydrosol during the collection period. The impinger has wall losses of about 35% for 7 µm AD particles (Kesavan et al 2010) as compared with about 10% losses in the Andersen for that same size (Rao and Whitby 1978). Kesavan et al (2010), in tests of SKC impingers that had Pantoea agglomerans (vegetative cells) spiked into the collection liquid, observed that about half of the cells were either lost to the impinger walls or rendered unculturable following operation of the impinger for 1 h subsequent to the spiking.…”
Section: Bioaerosol Sampled From a Classroommentioning
confidence: 99%
“…The impinger has wall losses of about 35% for 7 µm AD particles (Kesavan et al 2010) as compared with about 10% losses in the Andersen for that same size (Rao and Whitby 1978). Kesavan et al (2010), in tests of SKC impingers that had Pantoea agglomerans (vegetative cells) spiked into the collection liquid, observed that about half of the cells were either lost to the impinger walls or rendered unculturable following operation of the impinger for 1 h subsequent to the spiking. FAME bacteria isolate analyses, from a test in the classroom conducted subsequent to the primary sampling experiment, showed 6 strains in the proportions listed in Table 2.…”
Section: Bioaerosol Sampled From a Classroommentioning
confidence: 99%